2016
DOI: 10.2320/matertrans.m2015463
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Pure Na–X and Na–P Zeolite from Acid-Extracting Residues of CFB Fly Ash by a Single-Step Hydrothermal Method

Abstract: Acid-extracting residue of circulating uidized bed (CFB) y ash is still underutilized leaving disposal problems. In fact, high silica content inside this material opens a possibility to become a potential zeolites precursor. In this study, ne particles of acid residues have been reused to prepare zeolite Na-X and Na-P with high purity and intensity. Acid residue was used to synthesize zeolite Na-X and Na-P using a single-step hydrothermal process. The effects of crystallization time, temperature and sodium hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…When the hydrothermal time was increased to 12 h (Ht 2), the diffraction peak strength of C 2 S weakened, and the diffraction peak of the zeolite phases significantly increased in intensity. When the hydrothermal time was further extended to 24 h (Ht 4), the peak strength and peak type did not significantly change, indicating that the growth and dissolution of crystals reached dynamic equilibrium at this time 31 .
Figure 7 XRD patterns of hydrothermal products with different hydrothermal times; Ht 1: hydrothermal time at 6 h, Ht 2: hydrothermal time at 12 h, Ht 3: hydrothermal time at 18 h, Ht 4: hydrothermal time at 24 h.
…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…When the hydrothermal time was increased to 12 h (Ht 2), the diffraction peak strength of C 2 S weakened, and the diffraction peak of the zeolite phases significantly increased in intensity. When the hydrothermal time was further extended to 24 h (Ht 4), the peak strength and peak type did not significantly change, indicating that the growth and dissolution of crystals reached dynamic equilibrium at this time 31 .
Figure 7 XRD patterns of hydrothermal products with different hydrothermal times; Ht 1: hydrothermal time at 6 h, Ht 2: hydrothermal time at 12 h, Ht 3: hydrothermal time at 18 h, Ht 4: hydrothermal time at 24 h.
…”
Section: Resultsmentioning
confidence: 97%
“…Hydrothermal temperature also has a significant influence on the formation of zeolite. Higher temperatures can improve the concentration of chemical groups in the sol, which is conducive to zeolite crystallization 31 . Figure 8 shows the XRD patterns of zeolites prepared at different hydrothermal temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…It is reported that special templates or structure-directing agents were beneficial for the formation of zeolite during the hydrothermal condition . In this study, a self-made structure-directing agent was used for zeolite synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…It is reported that special templates or structure-directing agents were beneficial for the formation of zeolite during the hydrothermal condition. 28 In this study, a self-made structure-directing agent was used for zeolite synthesis. Figure 2 shows the XRD patterns of the Si/Al-gel and synthesized zeolites with different amounts of structuredirecting agent added (90 °C, NaOH concentration of 2.5 mol•L −1 , stirring for 3 h, and aging for 12 h).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…According to Ostwald rule of stages, the synthesis process of zeolites often undergoes the structural transformations from one metastable form to more thermodynamically stable form 24 . FAU‐type zeolite possesses the similar synthesis ratio with zeolite P. When crystallization T was 120°C, FAU‐type zeolite as a metastable phase would be preferentially crystallized in the Si‐rich synthesis system formed by the solubility of the raw materials 25 . When crystallization T was 130°C and 140°C, the metastable FAU‐type zeolite was dissolved and transformed to more thermodynamically stable zeolite P particles 26 .…”
Section: Resultsmentioning
confidence: 99%